PENGARUH VARIASI AGREGAT KASAR PENYUSUN BETON TERHADAP KERAPATAN BETON DENGAN MENGGUNAKAN PULSE VELOCITY PADA ALAT UPV (ULTRASONIC PULSE VELOCITY) - Putri, Enggie Herma; Wijatmiko, Indradi; Budio, Sugeng Prayitno (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Concrete has already get through many developments, one of them is technological ones with mixture combination of various materials. Due to various materials, it is necessary to test the concrete. One of the test is a non-destructive test or test without damaging the test object with a device called Ultrasonic Pulse Velocity (UPV). This study aims to determine the relation between compressive strength and the concrete velocity produced by UPV test. This study analyze the velocity, which is obtained from UPV testing on cylindrical specimens with different variations of aggregate. There are 4 types of variation in this study,Â fiber concrete, pumice concrete, porous concrete, and recycle concrete. In this study the relation between compressive strength and velocity produces coefficient of determination which is different on each variation of concrete.